TRADITIONAL PANCHAYATS IN JAUNSAR-BAWAR - Kalpna Kumari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The traditions in any society evolve over time, reflecting changes in circumstances. In tribal societies like Jaunsar-Bawar, cultural practices hold significant value, with the Syana and Khumdi systems serving as traditional panchayats. The British government recognized the uniqueness of the Syanachari system and granted legal rights to the Syanas, which helped with revenue collection and ensured smooth administrative functions. Although the Syanachari practice was abolished after independence, the Syana and Khumdi systems still retain social significance in Jaunsari society today.